Studi Case Control Pada Balita dengan Riwayat Berat Bayi Lahir Rendah (BBLR) terhadap Kejadian Kejang Demam di RSUD Provinsi NTB - Muhammad Hanif Imtiyaz; Rohmania Setiarini; Dewi Utary; Ananta Fittonia Benvenutto (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Case Control Study on Toddlers with a History of Low Birth Weight (LBW) on the Incidence of Febrile Seizures at the NTB Provincial Regional Hospital] Febrile seizure is defined as an occuranse of seizure in children aged 6 months to 5 years associated by an increase in temperature above 38oC that is not caused by an intracranial process. Febrile seizures are influenced by risk factors from within the baby itself such as low birth weight babies (LBW). The condition of immature organs and body fat insufficiency, make babies with LBW have a higher tendency to experience exposure to infections, and are unable to maintain their body temperature properly, thereby increasing the risk of having a fever attack. This research is a case-control study design with an analytic observational study. Purposive Sampling is used as the sampling technique. The research was conducted at the RSUD Provinsi NTB on August 29 2022 – September 1 2022. The data obtained was then analyzed using univariate analysis, and statistically tested using the Chi-Square test, with another alternative Fisher Exact Analysis. The significance value limit is (p-value = ?0.05). The Chi-Square test cannot be continued because there are numbers < 5 in a bivariate column. The alternative results of Fisher's test analysis showed that p-value = 0.311, H0 was accepted, there was no relationship between LBW history and the incidence of febrile seizures at the RSUD Provinsi NTB. The study concluded that statistically there was no significant relationship between LBW history and the incidence of febrile seizures at the RSUD Provinsi NTB.